FEATURES OF PHYSICAL DEVELOPMENT AND ADAPTATION CAPABILITIES OF THE CARDIORESPIRATORY SYSTEM IN CHILDREN AND TEENEGERS ENGAGED IN SWIMMING AND RHYTHMIC GYMNASTICS - Rakhmatova Fotima Utkirovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article examines the impact of regular physical activity, including swimming and rhythmic gymnastics, on the cardiorespiratory system, physical development. The aim of this study is to analyze the physical development and functional state of the cardiorespiratory system in children and adolescents involved in swimming and rhythmic gymnastics. A review of current scientific publications on the impact of systematic physical activity on anthropometric indicators, cardiovascular and respiratory performance, of young athletes is provided. It emphasizes the importance of developing comprehensive programs for assessing the body’s functional reserves to prevent noncommunicable diseases and ensure safe sports activities. A literature review revealed ambiguous effects of youth sports compared to physical education in the school curriculum, which requires further research.